The Role of Advocates in Handling Divorce Cases When the Plaintiff Is Not Present at The Decision Hearing - Mayca, Ofelica Ruth; Esther, July (Manunggal Halim Jaya, 2025)
In the context of family law, the presence of a competent advocate is essential to represent and protect the interests of the plaintiff. The advocate serves as the legal representative in court and ensures that the entire legal process runs smoothly and fairly even in the absence of the plaintiff. The advocate's duties consist of attending the judgment hearing, recording the contents of the judgment, communicating the result to the plaintiff and providing legal advice regarding the next steps to be taken including the filing of an appeal. Not only does this involve aspects of legal representation, but also the management of communication between the plaintiff and the court and the preparation of relevant documents. The results show that the role of advocates is essential in the legal process, providing certainty and protection of rights for plaintiffs and ensuring a fair and transparent legal process.